Learning about System Renewal - Levin, Ben; Fullan, Michael (http://lst-iiep.iiep-unesco.org/cgi-bin/wwwi32.exe/[in=epidoc1.in]/?t2000=027046/(100), 2008)
Incl. bibl., abstract Our focus in this article is on the lessons learned about effective change from international experience with large-scale reform over the last 20 years. The central lesson now evident is that sustained improvement in student outcomes requires a sustained effort to change teaching and learning practices in thousands and thousands of classrooms, and this requires focused and sustained effort by all parts of the education system and its partners. Key components of this work include a small number of ambitious yet achievable goals, publicly stated; a positive stance with a focus on motivation; multi-level engagement with strong leadership and a "guiding coalition"; emphasis on capacity building with a focus on results; keeping a focus on key strategies while also managing other interests and issues; effective use of resources; and constant and growing transparency including public and stakeholder communication and feedback. Although we believe the use of change knowledge is increasing internationally, future prospects remain mixed because the work is hard to do.